Precise, contactless measurements of the surface tension of picolitre aerosol droplets. Issue 1 (9th October 2015) - Bzdek, Bryan R.; Power, Rory M.; Simpson, Stephen H.; Reid, Jonathan P.; Royall, C. Patrick
Abstract : Precise measurements of the surface tension and viscosity of airborne picolitre droplets can be accomplished using holographic optical tweezers. Abstract : The surface composition and surface tension of aqueous droplets can influence key aerosol characteristics and processes including the critical supersaturation required for activation to form cloud droplets in the atmosphere. Despite its fundamental importance, surface tension measurements on droplets represent a considerable challenge owing to their small volumes. In this work, we utilize holographic optical tweezers to study the damped surface oscillations of a suspended droplet (<10 μm radius) following the controlled coalescence of a pair of droplets and report the first contactless measurements of the surface tension and viscosity of droplets containing only 1–4 pL of material. An advantage of performing the measurement in aerosol is that supersaturated solute states (common in atmospheric aerosol) may be accessed. For pairs of droplets starting at their equilibrium surface composition, surface tensions and viscosities are consistent with bulk equilibrium values, indicating that droplet surfaces respond to changes in surface area on microsecond timescales and suggesting that equilibrium values can be assumed for growing atmospheric droplets. Furthermore, droplet surfaces are shown to be rapidly modified by trace species thereby altering their surface tension. This equilibration of droplet surface tension to the local environmental conditions is illustrated for unknown contaminants in laboratory air and also for droplets exposed to gas passing through a water–ethanol solution. This approach enables precise measurements of surface tension and viscosity over long time periods, properties that currently are poorly constrained.